Control over the printed book: editorial censorship in the Kingdom of Navarre (1801-1833) - Ruiz Astiz, Javier (Huarte de San Juan. Geografía e Historia, 2018)
Navarre counted until 1841 with a control over the printed book exercised exclusively by Royal Council. One of the most obvious manifestations of this control was the civil censorship, to which the ecclesiastic was added. The exercise of that will allow us to verify its application and its different motivations, but also help us to unravel your intrahistory, approaching the protagonists of that work.